Growing old before growing rich: a scoping review on ageing-related policy interventions from the WHO Southeast Asian Region - Nachiket Gudi; Anu Mohan; Teddy Andrews Jaihind Jothikaran; Abhijith A K; Lena Ashok (BMJ Open)
Background WHO Southeast Asian Region (WHO SEARO) is home to 1.94 billion people accounting for one-fourth of the global population.Objective The primary objective of this scoping review is to describe the various policy interventions implemented in countries of the WHO SEARO to address the consequences of ageing.Design The Arksey and O’Malley framework for scoping review was used to explore existing policy interventions on aged care.Setting WHO SEARO.Methods Ten articles and 33 grey literature discussing the various aged care interventions adopted by WHO SEARO countries were identified through a comprehensive search performed across five databases, PubMed (NCBI), Embase (Elsevier), Web of Science (Clarivate) and Scopus (Elsevier) and Google Scholar.Results The review indicates that healthcare, long-term care and rehabilitation, maintenance and welfare, and old age social security are the critical domains of existing policy intervention. The grey literature, including policies, acts, legislations, agendas and plans of action adopted by WHO SEARO countries, concludes that existing interventions are spread across the differential aspects of ageing and aged care. The notable delimitations of the given policy interventions are ambiguity regarding the monitoring of the programmes, lack of benchmark standards for evaluation of progress, inadequate attention to rural poverty and lack of decentralisation.Conclusion WHO SEARO countries can respond better to ageing by reinforcing areas such as caregiver support and allowances, public financing in older care, old age health insurance, public-private partnership in mobile and institutional caring and social security systems including old age and disability pension.